2022
DOI: 10.1186/s41235-022-00382-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mask use on face recognition: an eye-tracking study

Abstract: We examined how mask use affects performance and eye movements in face recognition and whether strategy change reflected in eye movements is associated with performance change. Eighty-eight participants performed face recognition with masked faces either during learning only, during recognition only, or during both learning and recognition. As compared with the baseline condition where faces were unmasked during both learning and recognition, participants had impaired performance in all three scenarios, with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 59 publications
2
23
0
Order By: Relevance
“…In Study 2, we found that individuals with ASD had poorer performance than typical participants in the recognition of unmasked faces that were learned with a masked on. Hsiao et al ( 2022 ) showed that in this scenario, typical adults who adjusted their face-recognition strategies by shifting their gazes toward the eyes of the unmasked faces had better recognition performance. This shift in eye gaze strategy toward the eyes is beneficial in this scenario since these unmasked faces were learned with a mask on, revealing only the information around the eye region for memory encoding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Study 2, we found that individuals with ASD had poorer performance than typical participants in the recognition of unmasked faces that were learned with a masked on. Hsiao et al ( 2022 ) showed that in this scenario, typical adults who adjusted their face-recognition strategies by shifting their gazes toward the eyes of the unmasked faces had better recognition performance. This shift in eye gaze strategy toward the eyes is beneficial in this scenario since these unmasked faces were learned with a mask on, revealing only the information around the eye region for memory encoding.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, their strategy change during recognition would be mainly guided by the mask and rely less on cognitive flexibility or interference control, and thus no significant performance difference was observed between the two participant groups. Hsiao et al ( 2022 ) showed that in this scenario, typical adults whose eye fixation behavior was more consistent across trials had better performance, and this eye fixation behavior consistency was particularly correlated with non-verbal IQ as measured in the nine-item Raven’s test. Since in the current study the ASD and typical groups were matched in non-verbal IQ, the result that they did not differ in performance in this scenario was consistent with Hsiao et al’s finding ( 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Hwu et al (2021) compared heatmap-based XAI methods, LRP, with human attention data and reported a higher similarity to task-driven attentive human attention than inattentive attention. Note however that cogntive science research has consistently shown that human attention during image viewing are both task-specific (e.g., Borji and Itti 2015;Kanan et al 2015) and person-specific (e.g., Hsiao et al 2021a;An and Hsiao 2021;Hsiao et al 2021b;Hsiao, Liao, and Tso 2022). As the purpose of XAI is to provide explanations, comparing saliency-based XAI with human attention that are associated with better performance during an explanation task will provide more insights into the quality of XAI.…”
Section: Human Attention Datasets and Applicationsmentioning
confidence: 99%
“…To measure participants' eyemovement pattern in each condition along the dimension of the two representative group patterns, we defined A-B scale as A-B Scale = (A -B)/(jAj þ jBj), where A stands for the log-likelihood of the participant's eye-movement data being classified as the first pattern and B stands for the log-likelihood of the data being classified as the second pattern. A more positive A-B scale value indicates higher similarity to the first pattern as opposed to the second pattern (e.g.,Chan et al, 2018;Hsiao et al, 2022).Transparency and OpennessWe report how we determined our sample size, all manipulations, and all measures in the study. Data were analyzed using SPSS(Nie et al, 1975) and Jamovi(S ahin & Aybek, 2019).…”
mentioning
confidence: 99%